Exploring smallholder farm resilience to climate change: intended and actual adaptation - Hussein, Jaabir; Bilotto, Franco; Mbui, Damaris; Omondi, Philip; Harrison T.M; Crane, A. Todd; Sircely, Jason (Frontiers Media, 2024)
Low production potential of arid regions heightens vulnerability of farms to market shocks and extreme weather events. Here we examine African smallholder farmer perceptions of climate change, including perceived (intended) and actual adaptation strategies. We invoke survey questionnaires, focus group discussions, interviews and meteorological data to compare smallholder perceptions with actual weather events realised. We showed that most communities perceived climate change through the lens of perturbations to rainfall and temperature. Perceived increases in precipitation, indicated by 62% of respondents, and increased temperature, indicated by 77% of participants, aligned well with evidence shown by meteorological data. Around 88% of respondents identified prolonged drought as the most frequent extreme weather, followed by unseasonal rainfall (86% of respondents). Diversification of pasture fodder species and access to technology enabling timely weather forecasts were preferred actual and intended adaptation strategies, respectively. Recurrent and prolonged drought, spurious seasonalweather patterns, and lack of access to timely weather prognostics were the primary constraints to adoption of practices aimed at climate change adaptation. While farm size and practitioner experience were not associated with adaptive capacity, awareness of climate change impact potential and household income significantly influenced the rate and extent of adoption.We revealed amarked influence of gender in adaptation to the changing climate, with households where males made decisions exhibiting 76% adoption, compared with 34% of households adopting climate adaptations where decisions were made by females. Taken together, our study narrates critical roles of knowledge, finances, and gender in enabling or inhibiting adaptation to the climate crisis.